KETERKAITAN EARNING PER SHARE (EPS), CURRENT RATIO (CR), DAN DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM PERUSAHAAN - Jamaludin Jamaludin; Andi Hasryningsih Asfar; Ahmad Mukhlis (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The food and beverage company's earnings per share (EPS) share price and earnings are down in 2020. Current Ratio (CR) and Debt to Equity Ratio (DER) showed good progress, but neither was followed by an increase in stock prices. The purpose of this study is to determine the effect of Earnings Per Share (EPS), Current Ratio (CR), and Debt to Equity Ratio (DER) on stock prices both partially and simultaneously. This research uses a quantitative approach with secondary data in the form of Earning Per Share (EPS), Current Ratio (CR), and Debt to Equity Ratio (DER) data and stock prices. The determination of samples in this study used purposive sampling so that 9 companies from 29 food and beverage companies were obtained. The analysis technique used is a regression analysis technique of panel data using the help of the Eviews10 application. The conclusions obtained indicate that Earnings Per Share (EPS) partially have a positive and significant effect on the stock price. Current Ratio (CR) and Debt to Equity Ratio (DER) partially have no significant effect on stock prices. Earnings Per Share (EPS), Current Ratio (CR), and Debt to Equity Ratio (DER) simultaneously have a positive and significant effect on stock prices